661. In vitro Activity of Omadacycline and Comparator Antibiotics against Clostridioides difficile. (15th December 2022) - Skinner, Andrew M; Petrella, Laurica A; Cheknis, Adam K; Johnson, Stuart
Abstract: Background: Omadacycline was approved for the treatment of community acquired bacterial pneumonia (CABP) and acute bacterial skin and skin structure infections (ABSSSI) in 2018. Previous studies demonstrate that omadacycline has in vitro activity against Clostridioides difficile. We determined the in vitro activity of omadacycline and of comparator antimicrobials for the approved indications, CABP and ABSSSI, towards a contemporary and clinically relevant collection of C. difficile isolates. Methods: Antimicrobial agar dilution was performed on 200 clinical C. difficile isolates collected from 2014 – 2021. Isolates were selected based on the most prevalent restriction endonuclease analysis (REA) groups locally and nationally. Omadacycline was compared to 8 standard of care antimicrobials for CABP and ABSSSI: amoxicillin-clavulanate, azithromycin, ceftriaxone, clindamycin, doxycycline, linezolid, moxifloxacin, and trimethoprim-sulfamethoxazole. Results: Omadacycline demonstrated in vitro activity against all C. difficile isolates tested. The geometric mean MIC of omadacycline was 0.07 μg/ml and the MIC50 and MIC90 were 0.0625 μg/ml and 0.125 μg/ml, respectively. Among the comparator antibiotics, 52% of isolates were resistant to ceftriaxone and 37% of isolates were resistant to clindamycin. The majority of REA group BI isolates were resistant to clindamycin (77.7%, 28/36) and the clindamycin geometric mean MICs were higher for group BI compared to all other REA group strains (32 µg/ml and 5.33 µg/ml, respectively, p < 0.005). REA group BI also had elevated azithromycin and moxifloxacin geometric MICs (335.2 and 17.3 µg/ml, respectively). REA group DH isolates had higher trimethoprim-sulfamethoxazole geometric MICs compared to all other REA group strains (17.28 µg/ml and 8.14 µg/ml, respectively p >0.001). Nearly half of REA group BK isolates (47%) had MICs ≥2 µg/ml which did not correspond to elevated omadacycline MICs for the same isolates. Conclusion: Omadacycline demonstrated consistently low MICs against C. difficile when compared to approved antimicrobials for CABP and ABSSI which varied in activity among particular C. difficile strains. Omadacycline may reduce the risk of developing a C. difficile infection and requires further study. Disclosures: Stuart Johnson, M.D., Ferring Pharmaceuticals: Membership on Ferring Publication Steering Committee|Ferring Pharmaceuticals: Employee|Summit Plc: Advisor/Consultant.